2016
DOI: 10.1590/1516-4446-2015-1772
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of memory deficits is useful to distinguish between depression and mild cognitive impairment in the elderly

Abstract: Objective: To investigate whether the level of awareness of memory deficits is useful for discriminating between major depressive disorder (MDD) and mild cognitive impairment (MCI) in the elderly. Methods: Sixty-three consecutively referred patients (38 women and 25 men) with memory concerns comprising three groups (clinical control, MDD and MCI) underwent a memory test (Rey Auditory Verbal Learning Test [RAVLT]) and completed the Memory Assessment Complaints-Questionnaire (MAC-Q). Level of awareness was estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…In conclusion, patients with MDD show inaccurate memory selfawareness because they frequently and heavily report SMC while keeping relatively preserved memory tests, in contrast to patients with MCI-AD and healthy controls. Differential diagnosis between MDD and MCI-AD is a difficulty sometimes faced by clinicians (Coutinho et al, 2016). Although we found differences in memory awareness between the two conditions, it is at present unclear whether memory awareness might be clinically useful to discriminate between MDD and MCI-AD.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In conclusion, patients with MDD show inaccurate memory selfawareness because they frequently and heavily report SMC while keeping relatively preserved memory tests, in contrast to patients with MCI-AD and healthy controls. Differential diagnosis between MDD and MCI-AD is a difficulty sometimes faced by clinicians (Coutinho et al, 2016). Although we found differences in memory awareness between the two conditions, it is at present unclear whether memory awareness might be clinically useful to discriminate between MDD and MCI-AD.…”
Section: Discussioncontrasting
confidence: 58%
“…Statistically significant values (p < 0.05) in bold. MDD not only from patients with MCI, as reported by Coutinho et al (2016), but also from HC. It interesting to note that a previous study from Vannini and co-workers showed altered memory self-awareness in patients with MCI-AD, who would overestimate their memory function (Vannini et al, 2017).…”
Section: Discussionmentioning
confidence: 62%
“…Thirteen studies assessed the ACD as the discrepancy between subject's and informant's ratings of decline (Vogel et al, 2005 ; Onor et al, 2006 ; Ries et al, 2007 ; Orfei et al, 2010 ; Galeone et al, 2011 ; Spalletta et al, 2012 ; Maki et al, 2013 ; Zamboni et al, 2013 ; Ford et al, 2014 ; Jacus et al, 2015 ; Senturk et al, 2017 ; Tondelli et al, 2018 ; Oba et al, 2019 ). Four studies as the discrepancy between subjective and objective scores of cognitive functioning (O'Connell et al, 2014 ; Coutinho et al, 2016 ; Vannini et al, 2017a ; Hanseeuw et al, 2020 ). In Stites et al ( 2017 ), participants who responded affirmatively to any of the diagnosis-related questions were classified as “aware” of their diagnosis, whereas all others were coded “unaware.”…”
Section: Resultsmentioning
confidence: 99%
“…Out of a total of 20,136 studies, 20,088 were removed according to the exclusion criteria and, additionally, if they (a) assessed visuomotor abilities in patients with MCI in Parkinson's Disease (MCI-PD) because of the major motor impairment or (b) provided information about upper extremity functioning by self-report measures. The final set, therefore, consisted of 48 studies assessing the following issues: 16 studies assessed VSWM abilities [17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 12 studies assessed anosognosia for memory deficits [40][41][42][43][44][45][46][47][48][49][50][51], 14 studies assessed visuomotor abilities [52][53][54][55][56][57][58][59][60][61][62][63][64][65], 2 studies investigated the relationship between VSWM and conversion [37,66], and 4 studies investigated the relationship between anosognosia for memory deficit...…”
Section: Data Extraction Results and Synthesismentioning
confidence: 99%